CIDAN-XE: Computing in DRAM with Artificial Neurons - Singh, Gian; Wagle, Ankit; Khatri, Sunil; Vrudhula, Sarma (Frontiers in Electronics, 2022)
This paper presents DRAM-based processing-in-memory (PIM) architecture, called CIDAN-XE. It contains a novel computing unit called the neuron processing element (NPE). Each NPE can perform a variety of operations that include logical, arithmetic, relational, and predicate operations on multi-bit operands. Furthermore, they can be reconfigured to switch operations during run-time without increasing the overall latency or power of the operation. Since NPEs consume a small area and can operate at very high frequencies, they can be integrated inside the DRAM without disrupting its organization or timing constraints. Simulation results on a set of operations such AND, OR, XOR, addition, multiplication, etc., show that CIDAN-XE achieves an average throughput improvement of 72X/5.4X and energy efficiency improvement of 244X/29X over CPU/GPU. To further demonstrate the benefits of using CIDAN-XE, we implement several convolutional neural networks and show that CIDAN-XE can improve upon the throughput and energy efficiency over the latest PIM architectures.